Transcriptional profiling of dendritic cells matured in different osmolarities - Chessa, Federica (Genom Data, 2015)
Tissue-specific microenvironments shape the fate of mononuclear phagocytes [1–3]. Interstitial osmolarity is a tissue biophysical parameter which considerably modulates the phenotype and function of dendritic cells [4]. In the present report we provide a detailed description of our experimental workflow and bioinformatic analysis applied to our gene expression dataset (GSE72174), aiming to investigate the influence of different osmolarity conditions on the gene expression signature of bone marrow-derived dendritic cells. We established a cell culture system involving murine bone marrow cells, cultured under different NaCl-induced osmolarity conditions in the presence of the dendritic cell growth factor GM-CSF. Gene expression analysis was applied to mature dendritic cells (day 7) developed in different osmolarities, with and without prior stimulation with the TLR2/4 ligand LPS.